2022
DOI: 10.1787/1104143e-en
|View full text |Cite
|
Sign up to set email alerts
|

Policy responses to false and misleading digital content

Abstract: Unclassified OECD EDUCATION WORKING PAPERS SERIESOECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the author(s).Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcome, and may be sent to the Directorate for Education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Henderson et al (2012 [5]) found similarly in their study that volunteering in high school had a positive impact on students' political knowledge, interest, and involvement. However, they also identified that a positive volunteering experience as evaluated by the student is crucial to a service-learning programme's success.…”
Section: What Does the Research Say?mentioning
confidence: 86%
“…Henderson et al (2012 [5]) found similarly in their study that volunteering in high school had a positive impact on students' political knowledge, interest, and involvement. However, they also identified that a positive volunteering experience as evaluated by the student is crucial to a service-learning programme's success.…”
Section: What Does the Research Say?mentioning
confidence: 86%
“…(1) The initial inquest: the online "trending" information of the moment (2) The Apache.be investigation and new story (3) A zoom on a search scenario of use with the Dashboard (4) An explanation of a key algorithmic notion (5) The resolution: the disinformation risk avoided/dealt with (6) The MIL solutions and competences called for.…”
Section: Mil Methodology Research Design and Data Collectionmentioning
confidence: 99%
“…This structural knowledge gap points to the need for practical solutions, to step up the challenge of algorithm opacity by looking at the end-user (not the producer) and empowering citizens to analyse algorithms critically and creatively, in the hope of bringing insights in their own information consumption [4]. It calls for a bottom-up approach, with more Media and Information Literacy (MIL) strategies adjusted to algorithmic savviness, to make citizens more competent in their uses of online social media and their capacity to fight disinformation [5]. Scaling up citizen's agency is key to democratic societies capacity to harness the benefits of algorithms, useful as they may be, and downsize their negative effects on information quality, disinformation spread and platform transparency.…”
Section: Introductionmentioning
confidence: 99%
“…This can include supporting Interest-Driven Learning (Darling-Hammond et al, 2020 [162]). It can also support reframing schools as an "anchor institution" (Hildreth, 2012[163]; Mersand et al, 2019[164]) which values the "unique ability to strengthen civic life, understand and respond to community needs, and knit community members together through common experiences and shared interests" (Hildreth, 2012, p. 44 [163]).…”
Section: Ambition Loop: Institutions Within the Broader Societal Sect...mentioning
confidence: 99%